Relationship between perceived physical literacy and obesity-related outcomes in adolescents: the EHDLA study - Gabriel Domínguez-Martín; Pedro J. Tárraga-López; José Francisco López-Gil (Frontiers Media S.A., 2024)
PurposeThe aim of the present study was to examine the relationship between perceived physical literacy and obesity-related outcomes among adolescents from Spain.MethodsThis is a secondary cross-sectional analysis including a total sample of 845 Spanish adolescents (55.3% girls) aged 12-17 years from the Valle de Ricote (Region of Murcia) from the Eating Healthy and Daily Life Activities (EHDLA) project. Physical literacy was evaluated using the Spanish Perceived Physical Literacy Instrument for adolescents (S-PPLI). Body mass index was computed by taking the participants' body weight in kilograms and dividing it by the square of their height in meters, and body mass index (z score) and overweight/obesity and obesity were computed by the World Health Organization age- and sex-specific thresholds. Waist circumference was measured using a constant tension tape. Moreover, the waist-to-height ratio was calculated, and therefore, abdominal obesity was determined. Skinfold measurements were taken at the triceps and medial calf using calibrated steel calipers.ResultsIn general, the overall trend was downward (i.e., the higher the PPLI score the lower the obesity-related indicators), with the approximate significance of smooth terms being statistically significant for all models examined (p < 0.001). Adolescents with lower perceived physical literacy (PPL) showed the highest estimated marginal means of body mass index, body mass index z score, waist circumference, waist-to-height ratio, and skinfold (triceps and calf) and predictive probabilities of having excess weight, obesity, and abdominal obesity, while their counterparts with high PPL had the lowest. In addition, significant differences were observed for all the obesity-related indications between adolescents with low PPL and those with medium PPL (p-adjusted < 0.05 for all indicators), as well as with those with high PPL (p-adjusted < 0.05 for all indicators). Moreover, these significant differences were also shown for most indicators between adolescents with medium PPL and those with high PPL (except for obesity).ConclusionPhysical literacy could play a crucial role in maintaining more desirable obesity-related outcomes in adolescents. Adolescents with high perceived physical literacy showed lower obesity-related indicators (i.e., body mass index, body mass index z score, waist circumference, waist-to-height ratio, skinfolds), as well as a lower probability of having excess weight, obesity, and abdominal obesity.